2018
DOI: 10.1080/09537104.2018.1445837
|View full text |Cite
|
Sign up to set email alerts
|

Meal intake increases circulating procoagulant microparticles in patients with type 1 and type 2 diabetes mellitus

Abstract: Diabetes mellitus (DM) is associated with prothrombotic alterations, and postprandial hyperglycemia is an independent risk factor for cardiovascular complications. We therefore investigated whether a standardized mixed meal alters circulating microparticles (MPs) and their procoagulant activity in DM patients. Patients with DM type 1 (T1DM, n = 11) and type 2 (T2DM; n = 9) were studied before and 90 min after a standardized meal (without premeal insulin). MPs in plasma derived from platelets (PMPs), endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
1
13
0
2
Order By: Relevance
“…26,[35][36][37] A recent study suggested that the TF + and PS + MPs were associated with meal intake, and lipid-lowering agents in T1DM patients. 38 In our study, the elevated counts of TF + MPs in patients with T1DM, mostly derived from platelet, lymphocytes and endothelial cells, suggested a hypercoagulable state of T1DM patients. 39 TF + PS + MP count was higher in patients with established microvascular complications without an obvious signal of its subgroup.…”
Section: Discussionsupporting
confidence: 56%
“…26,[35][36][37] A recent study suggested that the TF + and PS + MPs were associated with meal intake, and lipid-lowering agents in T1DM patients. 38 In our study, the elevated counts of TF + MPs in patients with T1DM, mostly derived from platelet, lymphocytes and endothelial cells, suggested a hypercoagulable state of T1DM patients. 39 TF + PS + MP count was higher in patients with established microvascular complications without an obvious signal of its subgroup.…”
Section: Discussionsupporting
confidence: 56%
“…One study did not observe a variation of L-EV levels after a high fat meal while they used CD31-CD42b-CD62 markers to identify the endothelial L-EVs 55 . An acute increase of L-EV levels during the postprandial period was also observed in diabetic patients 58 , in individuals with cardiovascular risk 61 and in atherosclerotic patients 56 , all of them presenting already a higher fasting level of L-EVs when compared to healthy volunteers. It is noteworthy that the postprandial increase of L-EV levels had similar magnitude in individuals at CVD risk than in healthy volunteers 56 .…”
Section: The Postprandial Variation Of Circulating L-evsmentioning
confidence: 65%
“…Several subtypes of circulating L-EVs increased in response to fat intake: the endothelial L-EVs identified as CD31 + -CD42b -(+50-160 %) 53,54,59 , annexin V + -CD31 + -CD42b -(+30%) 51 , CD144 + (+ 20 %) 60 and CD144 + -CD62b -(+ 100-130 %) 47,48 EVs, and the platelet-derived L-EVs characterized as annexin V + -CD31 + -CD42b + 51 and CD41 + -CD61 + 56 EVs. Studies from Tushuizen et al 62 , Sustar et al 46 and Spectre et al 58 also showed that all annexin V + L-EVs increased postprandially after a high fat meal. One study did not observe a variation of L-EV levels after a high fat meal while they used CD31-CD42b-CD62 markers to identify the endothelial L-EVs 55 .…”
Section: The Postprandial Variation Of Circulating L-evsmentioning
confidence: 91%
See 1 more Smart Citation
“…Известно, что активированные тромбоциты способствуют развитию атеросклероза и его тромботических осложнений [22]. Различные механизмы могут способствовать активации тромбоцитов при СД: гипергликемии после приема пищи, гиперинсулинемии, воспалению, сопутствующим заболеваниям, таким как ожирение, а также усилению перекисного окисления липидов, приводящему к неферментативному образованию F2-изопростанов, которые обладают способностью действовать как агонисты рецептора TXA2 [22,[24][25][26]. Следует отметить, что описанные изменения тромбоцитов у пациентов с СД сохраняются и на фоне хорошего гликемического контроля [19,20].…”
Section: антиагреганты при сахарном диабетеunclassified